Differences in the results of examination for intestine worm infections before and after drug administration Worms in Students SDN Lantung Wori District North Minahasa Regency - Lalangpuling, Indra Elisabet; Odameng, Elisabet; Konoralma , Ketrina (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
Soil Transmitted Helminths worm infection is an intestinal worm infection transmitted through direct contact with contaminated eggs or parasitic worms in the soil. Treatment of worm infections can be done by administering deworming medication. The purpose of this study was to determine the results of the examination of Soil Transmitted Helminths (STH) worm eggs before and after administration of deworming medication. The sample population in this study were all students of SDN Lantung. The total sample in this study was 32 students consisting of grades 1 to 6. The research method was descriptive analytical with a cross-sectional design. The results of the study were obtained before the administration of deworming medication, Ascaris lumbricoides were found in 5 students (16.6%), Hookworms were found in 1 student (3.3%), and Hookworms were found in 1 student (6.6%). The results of the fecal examination after six months of deworming medication found Ascaris lumbricoides in 4 students (12.5%) and Hookworms in 1 student (3.3%). The administration of deworming medication in this study showed that there was a difference before and after administration of deworming medication in the feces of students at SDN Lantung.